2017
DOI: 10.1002/hbm.23824
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural correlates of irritability: Findings in a large healthy cohort

Abstract: Irritability and nonviolent aggression are common behavioral features across the population, yet there is limited neurobiological research into subclinical phenotypes representing the lower edge of a symptom continuum ranging from slight irritability to criminal violence. We studied brain structural correlates of irritability in a large healthy cohort to test the hypothesis of associations with fronto-limbic brain structures implicated in mood regulation. In a large multicenter effort, we recruited 409 mentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…However, these symptoms might suggest involvement of limbic or temporal structures in VSS. The hypometabolism of the superior temporal gyrus found in our study is in agreement with its role for irritability ( Besteher et al , 2017 ) and for thought suppression of pain ( Chehadi et al , 2018 ). The latter study further demonstrated involvement of the middle temporal gyrus in cognitive pain control, an area that also exhibited grey matter volume increase in VSS.…”
Section: Discussionsupporting
confidence: 90%
“…However, these symptoms might suggest involvement of limbic or temporal structures in VSS. The hypometabolism of the superior temporal gyrus found in our study is in agreement with its role for irritability ( Besteher et al , 2017 ) and for thought suppression of pain ( Chehadi et al , 2018 ). The latter study further demonstrated involvement of the middle temporal gyrus in cognitive pain control, an area that also exhibited grey matter volume increase in VSS.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiology and Psychiatric Sciences 547 -Violence was associated with cortical thinning in the prefrontal cortex (left medial inferior frontal and right lateral sensory motor cortex and surrounding association areas) and intraparietal sulcus bilaterally, irrespective of group -Cortical thinning in left inferior dorsolateral prefrontal regions (Brodmann's area 45) and in right medial dorsal ACC (Brodmann's areas 8, 6, 32, 24) was detected in the SCZ group compared with the non-SCZ groups, irrespective of violence -There are some overlapping (in motor cortices) but also differences in the areas associated with violence in the group of patients with SCZ (thinning of the sensory motor areas) and in subjects with antisocial personality disorder (thinning of the medial prefrontal cortices), compared to the groups with no history of violence Neuroanatomical observations made in people with schizophrenia are in line with results from non-clinical samples (Besteher et al, 2017;Nakagawa et al, 2017). Specifically, Nakagawa et al (2017) explored the brain structures underlying hostility in a large sample of young healthy subjects showing a positive correlation between hostility scores and regional grey matter density in the anterior midcingulate cortex (aMCC), which has been hence suggested as a specific neural node accounting for the cognitive aspect of hostility.…”
supporting
confidence: 72%
“…If anger is a state dimension, hostility is a trait leading to temperamental proneness to anger (Smith, 1994). Both hostility and anger are common behavioural features across non-clinical as well as clinical populations (Wang et al ., 2014; Fisher et al ., 2015; Besteher et al ., 2017).…”
mentioning
confidence: 99%
“…T1-weighted images were preprocessed in MATLAB (The MathWorks, Natick, MA) using Statistical Parametric Mapping, version 12 (SPM12; Wellcome Department of Cognitive Neurology, University of London) and the Computation Anatomy Toolbox (CAT) for SPM (CAT 12; Christian Gaser; Department of Psychiatry, University of Jena) with CAT12 default parameters, as described elsewhere 25 . Briefly, images were corrected for magnetic field inhomogenities, spatially normalized using the DARTEL algorithm 26 , and segmented into GM, white matter (WM), and cerebrospinal fluid (CSF).…”
Section: Methodsmentioning
confidence: 99%